Indios civilizados e escolarizados: a produção de uma outra condição de etnicidade - Marcilene da Silva (2003)
The study presented in this text has resulted of an attempt to understand the ways that indigenous groups of XIX century used in order to build theirs places inside the society of the eighty hundred years whose dominant order was lift from the civilizing aspiration. School that historically was identified as sign of civilization was seen as a privileged place of analyses once it permits to investigate the shock between the civilizatory project aspired by the eighty hundred elite and the conflictuous reality of the emergent relationship in different situations of contact between Indians and colonizers. This research was built from lectures of a set of documental sources relating to the indigenous history in that period. In order to realize this study it was chose the school for Indians of Nossa Senhora dos Anjos de Itambacuri settlement in the province of Minas Gerais into 1873 to 1889.